Deciduous Molar Morphology from the Neolithic Caves of the Meuse River Basin, Belgium - Frank L'Engle Williams; Rebecca L. George; Caroline Polet (Dental Anthropology Association, 2018)
Nearly 200 karstic caves of the Meuse River Basin of Belgium preserve collective burials dated to the Late Neolithic. The gnathic remains from five well preserved sites provide an opportunity to explore potential relationship among these cave burials. The cave burials of Hastière Caverne M, Hastière Trou Garçon C, Maurenne Caverne de la Cave, Sclaigneaux and Bois Madame are dated to circa 4,635 to 3,830 years BP. Dental casts from mandibular and maxillary deciduous molars are scored using the ASUDAS. Carabelli's trait varies from a small, Y-shaped depression to a full cusp, and the largest ones are found at Hastière Caverne M. The mandibular first molars have three to five cusps and the second molars have five, with one instance of six cusps at Bois Madame, which exceeds the range of variation for other dental traits. The hypoconulid ranges from small to very large. A metaconulid is absent or small. Although the results are contingent on idiosyncratic preservation, differences in the frequencies of traits exist between the earlier cave burial from Hastière Caverne M and the late/final Neolithic burials of Sclaigneaux and Bois Madame, the latter of which is the most variable in the expression of dental traits.